Curative Effect of Triphala in Medical and Dental Sciences : A Scientific Review - Deswal, Himanshu; Singh, Yogender; H.S.Grover; Bhardwaj, Amit; Shalu Verma (Innovare Journal Health Sciences, 2016)
Advances in the field of alternative medicine have promoted the use of various natural products. Conventional drugs usually provide effective antibiotic therapy for bacterial infections, but there is an increasing problem of antibiotic resistance and a continuing need for new inventions. Hence, herbal drugs are being preferred over synthetic antibiotics. Triphala is such product which has innumerable benefits in the field of medicine which has procured appreciable importance in clinical research. It consists of equal parts of the Emblica officinalis, Terminalia chebula, and Terminalia bellerica. It is an antioxidant-rich herbal formulation and possesses diverse beneficial properties. It is a widely prescribed Ayurvedic drug and is used in the ailments of all dosas. It is a polyherbal compound. It is necessary to corroborate the consistency of mixing or combining in attribute balance. The present review will focus on the comprehensive appraisal of Triphala and its several applications in medicine and dentistry.